Close the Gap: Accelerating Post-pandemic Recovery through Social Justice - Valerie Gilbert Ulep; Ma. Christina F. Epetia; Sonny N. Domingo (Philippine Institute for Development Studies (PIDS), 2022)
Socioeconomic disparities run deep in the Philippines, but the COVID-19 pandemic further exacerbated these inequities. Globally, there is a renewed sense of urgency to break these inequities and place social justice at the front and center of the post-COVID recovery. Social justice is about redressing power imbalances, assuring the protection of equal access to liberties, rights, and opportunities, and distributing the benefits, risks, and costs among peoples across generations. In this paper, we have examined the disproportionate impacts of the COVID-19 pandemic in the following sectors: health, labor and education, and environment. We have examined deep-seated structural and systems challenges that could explain these disparities. Avenues for insightful discourses and genuine reforms are needed to address concerns on human capital development and social protection and environment resilience and climate change.
Keywords: 330; social justice; inequality; COVID-19; social protection; labor; education; health; environment; resilience